2019
DOI: 10.1007/s00204-019-02487-6
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo developmental toxicity of diethylstilbestrol (DES) in rat evaluated by an alternative testing strategy

Abstract: In the present study, we evaluated an alternative testing strategy to quantitatively predict the in vivo developmental toxicity of the synthetic hormone diethylstilbestrol (DES). To this end, a physiologically based kinetic (PBK) model was defined that was subsequently used to translate concentration-response data for the in vitro developmental toxicity of DES, obtained in the ES-D3 cell differentiation assay, into predicted in vivo dose-response data for developmental toxicity. The previous studies showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…With these differences in molecular size and structure, DBA is able to bind to the AhR with a higher affinity than BaP, as measured in the AhR CALUX assay (Appendix B; see Supporting Information). This may also imply that DBA displays a higher intrinsic potential for interaction with other receptors present in the ES‐D3 cells, including the retinoic acid receptor and the estrogen receptor (ER) that are known to be potentially relevant in PDT (Adam et al, ; Dimopoulou et al, ; Louisse et al, ). Hence, future studies may consider the influence of structural features and size of PAHs, particularly those present in PS extracts, on their ability to activate receptors relevant for their embryotoxicity potency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With these differences in molecular size and structure, DBA is able to bind to the AhR with a higher affinity than BaP, as measured in the AhR CALUX assay (Appendix B; see Supporting Information). This may also imply that DBA displays a higher intrinsic potential for interaction with other receptors present in the ES‐D3 cells, including the retinoic acid receptor and the estrogen receptor (ER) that are known to be potentially relevant in PDT (Adam et al, ; Dimopoulou et al, ; Louisse et al, ). Hence, future studies may consider the influence of structural features and size of PAHs, particularly those present in PS extracts, on their ability to activate receptors relevant for their embryotoxicity potency.…”
Section: Discussionmentioning
confidence: 99%
“…With these differences in molecular size and structure, DBA is able to bind to the AhR with a higher affinity than BaP, as measured in the AhR CALUX assay (Appendix B; see Supporting Information). This may also imply that DBA displays a higher intrinsic potential for interaction with other receptors present in the ES-D3 cells, including the retinoic acid receptor and the estrogen receptor (ER) that are known to be potentially relevant in PDT (Adam et al, 2019;Dimopoulou et al, 2018;Louisse et al, 2011). Hence, future studies may consider the influence of structural features and size of For bioactivation of the PAHs and PAH-containing PS, the present study made use of hamster liver microsomes as it has been shown that they are more effective for bioactivation of these groups of substances in comparison with rat or mouse liver microsomes (Blackburn et al, 1986;Haugen & Peak, 1983;Hermann, 1981;Hermann et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Agapios Sachinidis and colleagues from the University of Cologne published a review about possibilities and limitations of stem cell-based test methods in pharmacology and toxicology (Sachinidis et al, 2019[ 18 ]). In recent years, much progress has been achieved concerning in vitro techniques of liver (Godoy et al, 2013[ 7 ]; Grinberg et al, 2014[ 10 ]; Leist et al, 2017[ 15 ]; Ghallab et al, 2016[ 6 ]), kidney (Sjögren et al, 2018[ 24 ]; Jiang et al, 2018[ 11 ]; Su et al, 2016[ 25 ]; Valente et al, 2012[ 26 ]; Lee et al, 2017[ 14 ]), neuronal (Keil et al, 2018[ 12 ]; Yang et al, 2018[ 28 ]; Colaianna et al, 2017[ 5 ]; Sisnaiske et al, 2014[ 23 ]) and developmental toxicity (Adam et al, 2019[ 2 ]; Bridges et al, 2019[ 3 ]; Abbott, 2019[ 1 ]). Particularly, in developmental and reproductive toxicity testing, large numbers of animals are needed for analysis of a single compound (Krug et al, 2013[ 13 ]).…”
Section: mentioning
confidence: 99%
“…Moreover, it should be well established at which concentration ranges a gold standard control should lead to positive and negative results. For example, acetaminophen (APAP) should lead to positive test results at concentrations of 1-2 mM, while concentrations below 0.1 mM should test negative in test methods for hepatotoxicity (Godoy et al 2013 In recent years, numerous in vitro tests have been developed, particularly for nephrotoxicity (Lee et al 2017;Jiang et al 2018;Sjögren et al 2018), neurotoxicity (Colaianna et al 2017;Sisnaike et al 2014;Reffatto et al 2018;Yang et al 2018;Keil et al 2018), developmental toxicity (Adam et al 2019;Krug et al 2013;Shinde et al 2017;Rempel et al 2015;Waldmann et al 2014) and hepatotoxicity (Godoy et al 2013(Godoy et al , 2015Grinberg et al 2014Grinberg et al , 2018Reif et al 2015;Leist et al 2017), often supported by methods of systems modeling (Hoehme et al 2010;Ghallab et al 2016;Vartak et al 2016;Jansen et al 2017). However, relatively little has been done to quantitatively evaluate how well in vitro/in silico methods resemble the in vivo situation.…”
mentioning
confidence: 99%
“…In recent years, numerous in vitro tests have been developed, particularly for nephrotoxicity (Lee et al 2017 ; Jiang et al 2018 ; Sjögren et al 2018 ), neurotoxicity (Colaianna et al 2017 ; Sisnaike et al 2014 ; Reffatto et al 2018 ; Yang et al 2018 ; Keil et al 2018 ), developmental toxicity (Adam et al 2019 ; Krug et al 2013 ; Shinde et al 2017 ; Rempel et al 2015 ; Waldmann et al 2014 ) and hepatotoxicity (Godoy et al 2013 , 2015 ; Grinberg et al 2014 , 2018 ; Reif et al 2015 ; Leist et al 2017 ), often supported by methods of systems modeling (Hoehme et al 2010 ; Ghallab et al 2016 ; Vartak et al 2016 ; Jansen et al 2017 ). However, relatively little has been done to quantitatively evaluate how well in vitro/in silico methods resemble the in vivo situation.…”
mentioning
confidence: 99%